1
$\begingroup$

Problem: If $X\sim\text{WN}(\mu,\sigma^2).$ Let then $Z$ be the process defined by \begin{equation} Z_t=\sum_{i=0}^na_iX_{t-i} \end{equation} for some coefficients $a_1,...,a_n\in\mathbb{R}$ with $a_0=1.$ Show that $\text{Cov}[Z_t,Z_{t+h}]=\text{Cov}[Z_s,Z_{s+h}]$ and that $\mathbb{E}[Z_t]=\mathbb{E}[Z_{t+h}].$

Attempt:

\begin{align} \text{Cov}[Z_t,Z_{t+h}]&=\mathbb{E}[Z_tZ_{t+h}]-\mathbb{E}[Z_t]\mathbb{E}[Z_{t+h}]\\ &=\mathbb{E}\left[\sum_{i=0}^{n}a_i^2X_{t-i}X_{t+h-i}\right]-\mathbb{E}\left[\sum_{i=0}^{n}a_iX_{t-i}\right]\mathbb{E}\left[\sum_{i=0}^{n}a_iX_{t+h-i}\right]\\ &=\mathbb{E}\left[\sum_{i=0}^{n}a_i^2X_{s-i}X_{s+h-i}\right]-\mathbb{E}\left[\sum_{i=0}^{n}a_iX_{s-j}\right]\mathbb{E}\left[\sum_{i=0}^{n}a_iX_{s+h-j}\right]\\ &=\mathbb{E}[Z_sZ_{s+h}]-\mathbb{E}[Z_s]\mathbb{E}[Z_{s+h}] = \text{Cov}[Z_s,Z_{s+h}]. \end{align} We can just replace $t$ with $s$ in $X_t$ for a weakly stationary time series, the mean and variance do not vary with time. Same reasoning can easily be done to show the expectations.

Question: Is this correct? It feels too easy that we can just replace things inside of expectations like that.

$\endgroup$
1
  • 2
    $\begingroup$ Yes, it is a trivial proof. You are allowed to change the name of the "bound variable" t to another name such as s. (Just like renaming a local variable inside a computer program does not affect the value the program returns). $\endgroup$ – noob2 Apr 17 at 18:37
2
$\begingroup$

Note that:

$$ Z_tZ_{t+h} = \left(\sum_{i=0}^{n}a_iX_{t-i}\right) \left(\sum_{j=0}^{n}a_jX_{t+h-j}\right) \not =\sum_{i=0}^{n}a_i^2X_{t-i}X_{t+h-i} $$

Yes, as the expectation operator is linear, all we need is for:

$$ E[X_{t-i}]=E[X_{s-i}]$$

and

$$ E[X_{t-i}X_{t+h-j}] = E[X_{s-i}X_{s+h-j}] $$

to hold for all $h$, $i$, and $j$.

$\endgroup$
2
  • $\begingroup$ Ah yes I missed that part. Will change. However the expectations you have written, that follows by the stationary property right? Nothing I need to prove. $\endgroup$ – Parseval Apr 17 at 20:07
  • $\begingroup$ Yes, $(t+h-j) - (t-i) = (s+h-j) - (s-i)=h+i-j$ is the common shift (for the covariance stationarity equality). $\endgroup$ – ir7 Apr 17 at 20:19

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.